Significant factors that influence the use and non-use of personal protective equipment (PPE) on construction sites—Supervisors' perspective - Aminu Darda'u Rafindadi; Madzlan Napiah; Idris Othman; Hamzh Alarifi; Usman Musa; Musa Muhammad (Ain Shams Engineering Journal, 2022)
Various factors can influence the use/non-use of PPE among construction workers. This paper investigates the significant factors that influence the use and non-use of PPE from the supervisors’ perspective and assesses general safety awareness about PPE. A survey questionnaire was the medium of data collection. The calculated validity of the instrument is 0.817 and 0.885 for the causes of use and non-use of PPE and awareness, respectively. Results show that 45% of the variance in the PPE level on construction sites is accounted for by the 25 predictors collectively, F (25,70) = 2.290, p < 0.001. It indicates that risk perception about the hazardous situation (β = −0.320, t = −2.928, p = 0.05), workers with safety training (β = −0.323, t = −2.664, p = 0.010), on-site safety supervision (β = 0.629, t = 4.823, p = 0.000), and employment status (β = 0.293, t = 2.602, p = 0.011) significantly predict the level of use of PPE on-site.